Hábitos auditivos em adolescentes - Chiarelli, Fernanda Gelsomini Villas Bôas François (2013)
The use of portable listening devices (PLD), among teenagers, has grown and caused an increase in time exposure to high sound pressure levels. Is important to know the hearing habits of a group of young people from a private school and a public school in the city of São Paulo and to verify the level of awareness about the potential hearing damage caused by improper and prolonged exposure to high levels of loudness in recreational activities in order to promote good hearing habits. Objective: to investigate the hearing habits of teenagers from 14 to 18 years of age regarding to the use of portable listening devices, situations experienced after the use of devices and hearing loss prevention measures. Method: This is a cross-sectional study in a population of adolescents between 14 and18 years of age. The questionnaire used was based on a research conducted by Zogby et al. (2006). Method: the questionnarie was given by the researcher and answered by the students at home. The descriptive results analysis and association analysis were carried out through the chi- square and the Fisher s exact tests . Results: the sample was constituted by 86 students from 14 to 18 years old. The results show that more than 73,9% of the students , males and females, and of the two schools use music portable devices with earphones. In general, boys use the PLD in a higher volume, during more hours and many times during a week. The answer pattern for girls from public schools is similar to the boys from private schools. The general pattern for both boys and girls, shows that the higher volume comes in association to a major frequency of use. 60% of the students use computer/ laptop with earphones. 100% of the girls from public school use VI mobile phone with earphones, in private schools we found 60% for girls and 72,6 % for boys. Girls are more inclined to reduce the time of using and the volume of the PLD. 50% frequent parties /shows / samba school rehearsal. The hearing symptoms and extra-symptoms aren t different between males and females. The girls from private school, regarding to the public school, showed a minor interest in using hearing protection, and to know the influence of the sound pollution and to participate of hearing health. The students that use PLD / mobile phones showed more need in rising the volume of the TV/ radio, beside saying ham and feeling more tired. The boys that are inclined to use hearing protection, demonstrate worry concerning to lose hearing. Conclusion: The use of portable listening devices with earphones and mobile phones is a common habit among teenagers. Go to parties and shows are, at least, part of the daily life of the half of the analysed public. The interference of these facts in the hearing health of this population is already noticed by part of it. Although this behavior is settled among adolescents, we can see a tendency to a change of habits and a worry in losing the hearing datas that can benefit the implementation of hearing health at schools